PENINGKATAN INTERAKSI SOSIAL MELALUI PENAYANGAN FILM INSPIRATIF DAN SENAM MASSAL DI DESA BENTENG HULU - Dian Iriani; Siti A’isah; Fitri Iska Yuliana (COVIT (Community Service of Health), 2022)
Benteng Hulu Village is a village located in Mempura District, Siak Regency, Riau Province. This village has 14 neighboring neighborhoods and 3 hamlets located not too far away. Looking at the village of Fort Hulu which seems to be quite lagging behind and the lack of social interaction. It can be seen from the residents who still don't know each other even though the places where they live are close together. Therefore, Riau University students want to change the habits of the village community and increase social interaction in Benteng Hulu Village by holding new activities after the Covid-19 shock. The method used is a field study method where the author is directly involved and goes into the field in activities in Desa Benteng Hulu. This Real Work Lecture is conducted within 1 month. From the activities carried out, two things are concluded, namely: 1). The community will interact with each other if there are fun social interaction activities, 2). The community can use film media and gymnastics to foster a high sense of social towards the local community. Keywords: Community Service, Social Interaction, Watching Movies, Gymnastics